[PP.LB02.03] IMPACT OF CUFF POSITIONING ON BLOOD PRESSURE MEASUREMENT ACCURACY. MAY A SPECIALLY DESIGNED CUFF MAKE A DIFFERENCE?. (September 2016) - Bilo, G.; Sala, O.; Perego, C.; Faini, A.; Gao, L.; Gluszewska, A.; Ochoa, J.E.; Pellegrini, D.; Zorzi, C.; Grillo, A.; Lonati, L.M.; Parati, G.
Abstract : Objective: It is recommended that during blood pressure measurement cuff bladder should be placed with its centre above brachial artery. This study investigated the size of error related to incorrect cuff positioning using auscultatory and oscillometric devices, the latter coupled with specially designed IntelliWrap cuff. Design and method: In 57 subjects with a wide range of blood pressures and arm circumferences blood pressure was measured repeatedly with correctly placed mercury device (reference) and with test devices (auscultatory and oscillometric) with the cuff placed on the other arm in one of the following positions: correct, rotated by 90° medially (auscultatory only), by 90° laterally or by 180°. Additionally the different cuff positions of auscultatory device were tested using cuffs inappropriately small in relation to arm circumference (undercuffing; N = 33). Results: Systolic and diastolic blood pressures were unaffected by incorrect cuff position when using auscultatory cuff of appropriate size. Conversely, with undercuffing, blood pressure was overestimated when the auscultatory device cuff was displaced by 90° laterally (systolic/diastolic blood pressure differences: 4.9 ± 4.6/4.0 ± 4.6 mmHg, p < 0.01) or by 180° (3.9 ± 5.4/4.2 ± 5.1 mmHg, p < 0.01, see figure). Incorrect placement of the IntelliWrap cuff had no effect on the accuracy of the oscillometric measurements vs. correctly positioned cuff (difference <1.5 mmHg, NS). Figure. Bland-Altman and correlation plot for SBP with auscultatory measurement in correct position versus incorrect (180°) position. Data obtained with properly sized cuff (upper panel) and with too small cuff (lower panel) are shown. Figure. No caption available. Conclusions: Incorrect cuff positioning may introduce a systematic overestimation of auscultatory blood pressure values, in particular when the cuff is too small in relation to arm circumference. No such overestimation is present when using a specifically designed cuff, also able to ensure a complete arm coverage over a wide range of circumferences.